Dutch healthcare professionals' opinion on vaccination and education to prevent infections in immunocompromised patients: A mixed-method study with recommendations for daily practice. Issue 11 (7th March 2019) - Doornekamp, L.; de Jong, W.; Wagener, M.N.; Goeijenbier, M.; van Gorp, E.C.M.
Highlights: Patients' knowledge of their immune status is scored insufficiently. Forty percent of respondents suggests to use education as tool to prevent infections. Frequency of discussing vaccines during patient consultations is low. There are opportunities to improve preventive care for immunocompromised patients. Abstract: Background: The fast-growing population of immunocompromised patients (ICP) is more vulnerable to infectious diseases, demanding strategies to protect them. These strategies seem inconsistent in available guidelines and in practices. We aim to evaluate healthcare professionals' (HCP) opinions on vaccination to reduce the number and severity of infections in ICP. Methods: A mixed-method study, with an exploratory sequential design, was performed. Medical specialists from various departments in a tertiary care center in the Netherlands were invited for semi-structured interviews to explore their perspective on preventive care of ICP. Topics that play a substantial role in daily practice for ICP were translated into a survey to gain insight into what extent opinions were generalizable to Erasmus Medical Center. Results: Surveys were completed by 689 HCP (43% of the invitees), 269 of them treated at least two ICP weekly on average and were considered eligible for further analysis. Quantitative data showed that according to 80 percent of HCP, preventive care for ICP can be improved. Education was chosen by 40 percent as the most important intervention to reduce the number and severity of infections. Vaccinations were valued as important by seventeen percent of HCP. Except for influenza, vaccinations were not regularly discussed during routine consultations. Difficulties to administer vaccinations were experienced by 75 percent of HCP. Conclusion: According to our respondents, education is the most promising intervention to reduce the number and severity of infections in ICP. To reach a higher vaccine uptake, we recommend HCP to address vaccinations more frequently during consultations and to search for solutions to alleviate barriers to vaccinate.